Analysis of the Potential Development of the Wanurejo Tourism Village, Magelang Regency, Central Java - Lintang Muliawanti; Annisa Zafirah; Athia Fidian (Urecol Journal. Part H: Social, Art, and Humanities, 2022)
Tourism is one of the most important pillars in the movement of the Indonesian economy. Wanurejo Village is one of the tourist villages located in Borobudur District, Magelang Regency which is one of the parts of the National Tourism Strategic Area (KSPN) of Borobudur Temple. The purpose of this study is to analyze the development of tourism potential in Wanurejo Village with the 4A approach (Attraction, Amenities, Ancillary and Accessibility). Data obtained by interview, observation and documentation and analyzed descriptively qualitatively. Based on the results, the development of tourism in the Wanurejo based on the supporting components of tourism cannot be said to be optimal. These findings are expected to be input to the local government as a reference for the development of the Wanurejo Tourism village as one of the buffer zones of Borobudur temple.